Psychology of human behavior and informational studies in memory institutions in Brazil and the United States - Santos, José Carlos Sales dos (Revista Fontes Documentais, 2023)
Discussing scientifically about human behavior represents a complex operation due to the specificities inherent to the theme. Scientific elaboration, within the scope of the human and social sciences, authorizes researchers and scholars to only present partial and provisional truths corresponding to the subjective components of individuals. Thus, the behavior of informational subjects subsists in specific trajectories and understand the world in a different way, giving them a myriad of interpretations. Variations in behavior may constitute obstacles to scientific investigations, but the cumulative character of research developed in various fields of knowledge, such as Psychology and Information Science, allow consistent advances in the analysis of behavioral operations in informational environments, such as memory institutions (Archives, Libraries and Museums). Therefore, the present communication sought to verify how memory institutions in Brazil and the United States guide informational subjects in the process of searching and retrieving content in their collections.